Are Microglial Cells the Regulators of Lymphocyte Responses in the CNS? - Almolda, Beatriz; González, Berta; Castellano, Bernardo (Frontiers in Cellular Neuroscience, 2015)
Infiltration of immune cells in the central nervous system is a common hallmark in different neuroinflammatory conditions. Accumulating evidences indicate that resident glial cells can establish a cross-talk with infiltrated immune cells, including T-cells, regulating their recruitment, activation and function within the CNS. Although the healthy CNS has been though to be devoid of professional dendritic cells (DCs), numerous studies have been reported the presence of a population of DCs in specific locations such as the meninges, choroid plexuses and the perivascular space. Moreover, the infiltration of DC-precursors during neuroinflammatory situations has been proposed, suggesting a putative role of these cells in the regulation of lymphocyte activity within the CNS. On the other hand, under determined circumstances, microglial cells are able to acquire a phenotype of DC expressing a wide range of molecules that equipped these cells with all the necessary machinery for the communication with T-cells. In this review we summarize the current knowledge on the expression of molecules involved in the cross-talk with T-cells in both microglial cells and DCs and discuss the potential contribution of each of these cell populations on the control of lymphocyte function within the CNS.